Highly efficient synthesis of flavones via Pd/C-catalyzed cyclocarbonylation of 2-iodophenol with terminal acetylenes. Issue 9 (13th April 2016) - Zhu, Fengxiang; Li, Yahui; Wang, Zechao; Wu, Xiao-Feng
Abstract : A highly efficient and selective Pd/C-catalyzed carbonylation reaction for the synthesis of flavones has been developed. Various flavone derivatives were isolated in excellent yields with excellent functional group tolerances. The catalyst is reusable, and no phosphine ligand or inert gas protection is needed. Abstract : A highly efficient and selective Pd/C-catalyzed ligand-free cyclocarbonylation reaction for the synthesis of flavones has been developed. Various flavone derivatives were isolated in excellent yields with excellent functional group tolerances. Additionally, catalyst reuse experiments were performed successfully as well.